Wayang Gaga as a Media of Creativity Education for Students at Nongkosawit 02 Elementary School Semarang - Setyaningrum, Heny; Jazuli, Jazuli; Triyanto, Triyanto (Universitas Negeri Semarang, 2019)
Wayang Gaga is a contemporary puppet made from grass. Wayang Gaga is staged with a simple story and triggers communication between the players and the audience. Wayang Gaga can be used as a medium for creativity education for children through the process of creating and appreciating. This study aims to examine Wayang Gaga as a medium for creativity education for elementary school children. Research location in Nongkosawit Public Elementary School 02, Jl. Randusari, RT.06/RW.02, Nongkosawit, Gunungpati District, Semarang City. Data collection techniques use observation, interviews, and documentation. The data validation technique uses source triangulation. Data analysis techniques refer to Miles and Huberman with data reduction procedures, data presentation and conclusion drawing. The results showed that Wayang Gaga can be used as a medium for creativity education for elementary school children through the process of making puppets (creations) to short performances by students (appreciation). Weaving skills, the breadth of thinking and the flexibility of speaking in public when being a puppeteer is one of the characteristics of creativity that results from learning activities using the Wayang Gaga media. Specific creativity can be seen from the personalities of students involved in a series of creative processes namely Wayang Gaga workshops and performances, supported by internal and external driving factors, so as to produce a creative product in the form of Wayang Gaga and its performances. This research is expected to bring up new educational media based on local wisdom, so that in addition to developing creativity students can also recognize and love the arts in their own area.